Rab29 activation of the Parkinson's disease‐associated LRRK2 kinase. (15th January 2019) - Purlyte, Elena; Dhekne, Herschel S; Sarhan, Adil R; Gomez, Rachel; Lis, Pawel; Wightman, Melanie; Martinez, Terina N; Tonelli, Francesca; Pfeffer, Suzanne R; Alessi, Dario R
Abstract :